The Law of Competition in Digital Lean Startup - Lyu, Xuehai; Lyu, Wenbo (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
This paper discusses in detail the "law of the jungle" for startup success from five aspects, namely, risk identification (opportunity identification and shaping), tribe building (team building), combat readiness (technical product customer market), planning blueprint (business model expansion) and initial counter-attack (lean startup). Based on multiple case studies, it is explained how to achieve success in these areas. In the entrepreneurial process, opportunities need to be identified, a team needs to be built, initial validation of product technology and market needs to be conducted, business models need to be developed, and a keen sense of observation needs to be maintained. Determining the product or technology path includes short-term, mid-term, and long-term goals and plans, which helps entrepreneurial companies effectively attract capital, resources, and capabilities. The article emphasizes how businesses should build their business blueprints through expanding profits, using business model tools, and promoting sustainable development.